The Criteria of Humanity in the Qur’an based on Tafsir al-Mizān - ali asghar zakui (پژوهش نامه معارف قرآنی, 2011)
From a Quranic perspective, the Creator has honored man and has made him His successor on the earth. This paper attempts to find the criteria of humanity in the Qur’an, relying on Tafsir al-Mizān. The Qur’an introduces a triangle of criteria: faith, righteous deed and knowledge. Man can reach perfection solely when he has both faith and righteous deeds and he will be promoted to a higher spiritual rank only when these two qualities are completed with knowledge. In Quranic logic, only the knowledge that adds to the learned man’s modesty is one of the criteria of humanity. It is merely through the logical and balanced interaction between these three qualities that one becomes a perfect man who satisfies the standards and criteria set by the Qur’an. The fulfillment of these criteria will result in a pure life in this world and prosperity in the Hereafter.